PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM - Fairuz Awwabi Ahmad; Vika Fitranita; indah oktari wijayanti; Media Kusumawardani (UNIB Press, 2024)
This research aims to examine the influence of accounting information system and financial literacy have an effect on the performance of MSME users of OASSE the point of sale financial application. This research uses sensus technique with quantitative approach method. The data collection method is primary data obtained from distributing questionnaires to 45 respondents who are MSME owners that use OASSE the point of sale financial application. The data analysis technique used multiple linear regression analysis with SPSS program. The results showed that (1) Accounting information system has a positife effect on the performance of MSME users of OASSE the point of sale financial application (2) Financila literacy has a positife effect on on the performance of MSME users of OASSE the point of sale financial application.